The Covid-19 trade contraction: A view from global shipping, the EU and China - Sonali Chowdhry; Gabriel Felbermayr; Vincent Stamer (Kiel Institute for the World Economy (IfW), 2020)
This policy brief examines the effects of the Covid19 pandemic on international trade. Major exporting economies have posted record year-over-year monthly declines in export volume ranging from -7.9% in Germany to -24.3% in South Korea. While logistical bottlenecks are being solved, low demand puts pressure on trade activity. The shipping industry has reduced its activity around Europe, Asia and America by up to -10% pointing to a prolonged reduction in trade. Over the first quarter of 2020, China's trade contracted severely with most economies - particularly Canada, Japan, Russia, Italy and South Africa.The trade collapse affects businesses differently and especially hits those firms that participate in low-value added stages of global value chains by assembling components.
Keywords: 330; Trade; Covid-19; China; GVCs; Handel